Management of patients with lymphoma and COVID‐19: Narrative review and evidence‐based practical recommendations - Passamonti, Francesco; Nicastri, Emanuele; Di Rocco, Alice; Guarini, Attilio; Ibatici, Adalberto; Luminari, Stefano; Mikulska, Malgorzata; Visco, Carlo (Hematological oncology, 2023)
Patients with hematologic malignancies can be immunocompromized because of their disease, anti‐cancer therapy, and concomitant immunosuppressive treatment. Furthermore, these patients are usually older than 60 years and have comorbidities. For all these reasons they are highly vulnerable to infection with severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) and have an increased risk of developing severe/critical Coronavirus disease 2019 (COVID‐19) compared to the general population. Although COVID‐19 vaccination has proven effective in reducing the incidence of severe/critical disease, vaccinated patients with lymphoma may not be protected as they often fail to develop a sufficient antiviral immune response. There is therefore an urgent need to address the management of patients with lymphoma and COVID‐19 in the setting of the ongoing pandemic. Passive immunization with monoclonal antibodies against SARS‐CoV‐2 is a currently available complementary drug strategy to active vaccination for lymphoma patients, while monoclonal antibodies and antiviral drugs (remdesivir, ritonavir‐boosted nirmatrelvir, and molnupiravir) have proven effective in preventing the progression to severe/critical COVID‐19. In this narrative review we present the most recent data documenting the characteristics and outcomes of patients with concomitant lymphoma and COVID‐19. Our ultimate goal is to provide practice‐oriented guidance in the management of these vulnerable patients from diagnosis to treatment and follow‐up of lymphoma. To this purpose, we will first provide an overview of the main data concerning prognostic factors and fatality rate of lymphoma patients who develop COVID‐19; the outcomes of COVID‐19 vaccination will also be addressed. We will then discuss current COVID‐19 prophylaxis and treatment options for lymphoma patients. Finally, based on the literature and our multidisciplinary experience, we will summarize a set of indications on how to manage patients with lymphoma according to COVID‐19 exposure, level of disease severity and former history of infection, as typically encountered in clinical practice.